PENINGKATAN KEMAMPUAN HASIL BELAJAR STATISTIKA MATA PELAJARAN MATEMATIKA DENGAN COOPERATIVE LEARNING TIPE THINK-PAIR-SQUARE PADA SISWA KELAS XII MULTIMEDIA 3 SMK NEGERI 1 BANGIL KABUPATEN PASURUAN TAHUN PELAJARAN 2018/2019 - Sujiyono, Sujiyono (CV Sintesia, 2025)
In learning mathematics on basic competencies, determining the value of statistical data concentration is often a problem, especially for students of class XII Multimedia 3 at SMK Negeri 1 Bangil. It is known that the main problem of learning mathematics in class XII Multimedia 3 at SMK Negeri 1 Bangil is the ability to determine the value of statistical data concentration is still low. Based on these problems the researchers tried to present the use of the Think-Pair-Square Type of Cooperatie Learning learning model to better find and apply the concept acquisition, so the researchers took the problem of How to Improve Statistics Learning Outcomes Through the Application of the Think-Pair-Square Type Learning Model in Class XII Multimedia Students 3 State Vocational High School 1 Bangil, Pasuruan Regency, 2018/2019 Academic Year? From the problem, the researcher obtained data from observations and reflections. Based on the improvement observation data, it was found that there was an increase in student achievement in the first cycle, there were 21 students (58.33%) achieving a mastery score of > 70 with a class average of 77.78 while in Cycle II, 33 students (91.7%) achieved a grade completeness is > 78 with a class average of 85.42. From the results of learning improvements carried out by researchers, it can be concluded that the use of the Think-Pair-Square Type Learning Model can improve student achievement in class XII Multimedia 3 SMK Negeri 1 Bangil. This shows that the Think-Pair-Square Type Learning Model used by researchers is proven to be able to improve student achievement in class XII Multimedia 3 Semester 1 basic competence determines the value of statistical data concentration in class XII Multimedia 3 SMK Negeri 1 Bangil in the 2018/2019 academic year.